Preliminary study on abundance of aquatic insects in Sungai Sat, Taman Negara Pahang, Malaysia - Hasmi, Nur Atirah; Taib, Nurul Izza; Abdul Aziz, Rosmawati; Alwi, Habsah; Musa, Mohibah; Zainal, Safari (Universiti Teknologi MARA (UiTM), 2023)
The abundance of aquatic insects has been studied in seven (7) points at Sungai Sat, Pahang, Malaysia, specifically in Orang Asli settlements along with Sungai Sat. The focuses are to identify the aquatic insect families, to compare the abundance of aquatic insects in seven sampling areas and to investigate the effect of physical factors (water temperature, water depth, and water velocity) and chemical factors (pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD)) of streams on the abundance of aquatic insects. The samples were collected by using kicking sampling techniques using an aquatic net for two days. Physicochemical parameters have been measured in situ and recorded. Pearson Correlation analysis has been used to measure the association between physicochemical parameters and the abundance of aquatic insect communities. A total of 731 individuals were classified into 7 orders, and 19 families of aquatic insects were identified. The largest percentage of samples collected is from the order Ephemeroptera 49.5%, and the least is Blattodea 0.1%. The aquatic insects collected from Tanjung Sami have the highest abundance of 170 individuals from 5 orders and 8 families. Tanjung Sami has a moderate stream flow (0.6 m/s) with a water temperature of 27.21oC, 0.8 m depth, pH value of 8.08, DO level of 91.8%, BOD level of 6 mg/L, and COD level of 34 mg/L. The results reveal that the abundance of aquatic insects is high in moderate water temperature, deeper water, low water velocity, neutral range of water pH value, optimum dissolved oxygen (DO) level, and clean river.